A Note on the Variation in Wood Density in some 36-year-old Teak Trees from Different Seed Origins - Purkayastha, S. K.; Tandon, R. D.; Ramesh Rao, K. (Indian Forester, 1973)
Study of some increment cores from 36-year-old teak trees from four seed origins grown in South Coimbatore, indicates that seed source may have a significant effect on the density of the mature wood. Increment cores from trees of two of the seed origins were also studied from another locality viz. Nilambur. Analysis of the data from these two localities suggests that the influence of environment on wood density may be greater than that of seed origin.